Whole‐genome sequencing and antigenic analysis of the first equine influenza virus identified in Turkey. Issue 3 (8th February 2018) - Gahan, Jacinta; Garvey, Marie; Gildea, Sarah; Gür, Emre; Kagankaya, Anil; Cullinane, Ann
Abstract : Background: In 2013, there was an outbreak of acute respiratory disease in racehorses in Turkey. The clinical signs were consistent with equine influenza (EI). Objective: The aim was to confirm the cause of the outbreak and characterise the causal virus. Methods: A pan‐reactive influenza type A real‐time RT‐PCR and a rapid antigen detection kit were used for confirmatory diagnosis of equine influenza virus (EIV). Immunological susceptibility to EIV was examined using single radial haemolysis and ELISA. Antigenic characterisation was completed by haemagglutinin inhibition using a panel of specific ferret antisera. Genetic characterisation was achieved by whole‐genome sequencing using segment‐specific primers with M13 tags. Results: A H3N8 EIV of the Florida clade 2 sublineage (FC2) was confirmed as the causal agent. The index cases were unvaccinated and immunologically susceptible. Phylogenetic analysis of the HA1 and NA genes demonstrated that A/equine/Ankara/1/2013 clustered with the FC2 strains circulating in Europe. Antigenic characterisation confirmed the FC2 classification and demonstrated the absence of significant drift. Whole‐genome sequencing indicated that A/equine/Ankara/1/2013 is most closely related to the viruses described as the 179 group based on the substitution I179V in HA1, for example A/equine/East Renfrewshire/2/2011, A/equine/Cambremer/1/2012 and A/equine/Saone et Loire/1/2015. The greatest diversity was observed in the NS1 segment and the polymerase complex. Conclusions: The first recorded outbreak of EI in Turkey was caused by an FC2 virus closely related to viruses circulating in Europe. Antigenic and genetic characterisation gave no indication that the current OIE recommendations for EI vaccine composition require modification.